Association between venous thromboembolism rates and different prophylactic anticoagulation regimens in patients undergoing free flap reconstruction of the head and neck region - Saadoun, Rakan; Bengur, Fuat Baris; Moroni, Elizabeth A.; Surucu, Yusuf; Veit, Johannes Adrian; Sadick, Haneen; Smith, Roy E.; Kubik, Mark; Sridharan, Shaum; Solari, Mario G. (Microsurgery, 2023)
Background Venous Thromboembolism (VTE) is a serious complication after free tissue transfer to the head and neck (H&N). However, an optimal antithrombotic prophylaxis protocol is not defined in the literature. Enoxaparin 30 mg twice daily (BID) and heparin 5000 IU three times daily (TID) are among the most commonly used regimens for chemoprophylaxis. However, no studies compare these two agents in the H&N population. Methods A cohort study of patients who underwent free tissue transfer to H&N from 2012 to 2021 and received either enoxaparin 30 mg BID or Heparin 5000 IU TID postoperatively. Postoperative VTE and hematoma events were recorded within 30 days of index surgery. The cohort was divided into two groups based on chemoprophylaxis. VTE and hematoma rates were compared between the groups. Results Out of 895 patients, 737 met the inclusion criteria. The mean age and Caprini score were 60.6 [SD 12.5] years and 6.5 [SD 1.7], respectively. 234 [31.88%] were female. VTE and hematoma rates among all patients were 4.47% and 5.56%, respectively. The mean Caprini score between the enoxaparin (n = 664) and heparin (n = 73) groups was not statistically significant (6.5 ± 1.7 vs.6.3 ± 1.3, p = 0.457). The VTE rate in the enoxaparin group was significantly lower than in the heparin group (3.9% vs. 9.6%; OR: 2.602, 95% CI: 1.087-6.225). Hematoma rates were similar between the two groups (5.5% vs. 5.6%; OR: 0.982, 95% CI: 0.339-2.838). Conclusions Enoxaparin 30 mg BID was associated with a lower VTE rate while maintaining a similar hematoma rate compared to heparin 5000 units TID. This association may support the use of enoxaparin over heparin for VTE chemoprophylaxis in H&N reconstruction.
Online veröffentlicht: 27. Februar 2023
Gesehen am 06.08.2024